FOXP2. Issue 5 (13th August 2013) - Nudel, Ron; Newbury, Dianne F
Abstract : The forkhead box P2 gene, designated FOXP2, is the first gene implicated in a speech and language disorder. Since its discovery, many studies have been carried out in an attempt to explain the mechanism by which it influences these characteristically human traits. This review presents the story of the discovery of the FOXP2 gene, including early studies of the phenotypic implications of a disruption in the gene. We then discuss recent investigations into the molecular function of the FOXP2 gene, including functional and gene expression studies. We conclude this review by presenting the fascinating results of recent studies of the FOXP2 ortholog in other species that are capable of vocal communication. WIREs Cogn Sci 2013, 4:547–560. doi: 10.1002/wcs.1247 This article is categorized under: Psychology > Language Neuroscience > Genes, Molecules, and Cells